Short‐term interleukin‐37 treatment improves vascular endothelial function, endurance exercise capacity, and whole‐body glucose metabolism in old mice. Issue 1 (21st November 2019) - Ballak, Dov B.; Brunt, Vienna E.; Sapinsley, Zachary J.; Ziemba, Brian P.; Richey, James J.; Zigler, Melanie C.; Johnson, Lawrence C.; Gioscia‐Ryan, Rachel A.; Culp‐Hill, Rachel; Eisenmesser, Elan Z.; D'Alessandro, Angelo; Dinarello, Charles A.; et al.
Abstract: Aging is associated with vascular endothelial dysfunction, reduced exercise tolerance, and impaired whole‐body glucose metabolism. Interleukin‐37 (IL‐37), an anti‐inflammatory cytokine of the interleukin‐1 family, exerts salutary physiological effects in young mice independent of its inflammation‐suppressing properties. Here, we assess the efficacy of IL‐37 treatment for improving physiological function in older age. Old mice (26–28 months) received daily intraperitoneal injections of recombinant human IL‐37 (recIL‐37; 1 µg/200 ml PBS) or vehicle (200 ml PBS) for 10–14 days. Vascular endothelial function (ex vivo carotid artery dilation to increasing doses of acetylcholine, ACh) was enhanced in recIL‐37 vs. vehicle‐treated mice via increased nitric oxide (NO) bioavailability (all p  < .05); this effect was accompanied by enhanced ACh‐stimulated NO production and reduced levels of reactive oxygen species in endothelial cells cultured with plasma from IL‐37‐treated animals ( p  < .05 vs. vehicle plasma). RecIL‐37 treatment increased endurance exercise capacity by 2.4‐fold, which was accompanied by a 2.9‐fold increase in the phosphorylated AMP‐activated kinase (AMPK) to AMPK ratio (i.e., AMPK activation) in quadriceps muscle. RecIL‐37 treatment also improved whole‐body insulin sensitivity and glucose tolerance ( p  < .05 vs. vehicle). Improvements in physiological function occurred without significant changes in plasma, aortic, and skeletal muscle pro‐inflammatory proteins (under resting conditions), whereas pro‐/anti‐inflammatory IL‐6 was greater in recIL‐37‐treated animals. Plasma metabolomics analysis revealed that recIL‐37 treatment altered metabolites related to pathways involved in NO synthesis (e.g., increased L‐arginine and citrulline/arginine ratio) and fatty acid metabolism (e.g., increased pantothenol and free fatty acids). Our findings provide experimental support for IL‐37 therapy as a novel strategy to improve diverse physiological functions in old age. Abstract : Physiological function declines with aging, increasing risk of chronic diseases and disability. We show for the first time that treatment with a novel anti‐inflammatory compound interleukin‐37 (IL‐37) improves multiple physiological functions in old mice, and identify potential roles of reduced superoxide production, improved oxidative metabolism and circulating factors in mediating improvements. Our findings support IL‐37 therapy as a novel strategy for improving diverse physiological functions in old age.